1993
DOI: 10.1111/j.1365-2621.1993.tb03246.x
|View full text |Cite
|
Sign up to set email alerts
|

Water and Glycerol as Plasticizers Affect Mechanical and Water Vapor Barrier Properties of an Edible Wheat Gluten Film

Abstract: Glycerol improved film extensibility but reduced film puncture strength, elasticity, and water vapor barrier properties. The plasticizing effect of water was highly temperature dependent. During hydration of gluten film, a sharp decrease in puncture strength, elasticity, and an increase of extensibility and water vapor transmission rate were observed at 5, 30 and 5o'C for respective water contents of 30 (0,8 a,), 15 (0,7 a,) and 5% (0,4 a,). This was related to disruptive waterpolymer hydrogen bonding and glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
464
5
71

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 804 publications
(602 citation statements)
references
References 23 publications
40
464
5
71
Order By: Relevance
“…These interactions has been reported to improve the strength and elasticity of WG based films. 33 In this study we used potato starch with a slightly increased amylose content (27%), also containing modified amylopectin structure, which as expected, showed that a careful selection of plasticizer (in this case combination of glycerol and water) together with optimal extrusion temperature (such as 130°C or even higher) is needed in order to obtain a homogenous composite. High amylose potato starch (amylose content 86%) is known to have a higher viscosity compared to normal potato starch.…”
Section: Mechanical Properties Of Protein-starch Composites: the Effesupporting
confidence: 54%
“…These interactions has been reported to improve the strength and elasticity of WG based films. 33 In this study we used potato starch with a slightly increased amylose content (27%), also containing modified amylopectin structure, which as expected, showed that a careful selection of plasticizer (in this case combination of glycerol and water) together with optimal extrusion temperature (such as 130°C or even higher) is needed in order to obtain a homogenous composite. High amylose potato starch (amylose content 86%) is known to have a higher viscosity compared to normal potato starch.…”
Section: Mechanical Properties Of Protein-starch Composites: the Effesupporting
confidence: 54%
“…A obtenção dos mesmos, assim como a de coberturas biodegradáveis, está baseada na dispersão ou solubilização dos biopolímeros em um solvente (água, etanol ou ácidos orgânicos) e acréscimo de aditivos (plastificantes ou agentes de liga) obtendo-se uma solução ou dispersão filmogênica. Após o preparo, estas coberturas devem passar por uma operação de secagem para a formação dos filmes ou coberturas tipo casting (GONTARD; GUILBERT;CUQ, 1992).…”
Section: Palavras-chaves: Mandioca; Filmes; Amidos Modificados; Viscounclassified
“…Biodegradable and edible films from wheat proteins are useful in food packaging provided they are flexible, strong, heat sealable, and relatively transparent [36]. The mechanical and barrier properties of wheat gluten films have been studied [9,14,18]. An edible wheat gluten film was developed and the effects of gluten and ethanol concentrations and pH of the film-forming solution on various film properties, were evaluated [17].…”
Section: -Introductionmentioning
confidence: 99%